2022
DOI: 10.3390/ijms23020669
|View full text |Cite
|
Sign up to set email alerts
|

The Brain–Skin Axis in Psoriasis—Psychological, Psychiatric, Hormonal, and Dermatological Aspects

Abstract: Psoriasis is a chronic inflammatory skin disease with systemic manifestation, in which psychological factors play an important role. The etiology of psoriasis is complex and multifactorial, including genetic background and environmental factors such as emotional or physical stress. Psychological stress may also play a role in exacerbation of psoriasis, by dysregulation of the hypothalamic–pituitary–adrenal (HPA) axis, sympathetic–adrenal–medullary axis, peripheral nervous system, and immune system. Skin cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 162 publications
0
50
0
Order By: Relevance
“…Psoriasis is regulated by the brain–skin axis. The HPA axis is involved in the development of psoriasis by the release of CRH, ACTH, and glucocorticoids, and these regulate the skin response to stress and the topical immune response ( 100 ). MCs express CRHR1 in proximity of psoriatic plaques, and elevated CRH in psoriasis induces the degranulation of MCs.…”
Section: Contribution Of Mast Cells To the Immunopathogenesis Of Psor...mentioning
confidence: 99%
“…Psoriasis is regulated by the brain–skin axis. The HPA axis is involved in the development of psoriasis by the release of CRH, ACTH, and glucocorticoids, and these regulate the skin response to stress and the topical immune response ( 100 ). MCs express CRHR1 in proximity of psoriatic plaques, and elevated CRH in psoriasis induces the degranulation of MCs.…”
Section: Contribution Of Mast Cells To the Immunopathogenesis Of Psor...mentioning
confidence: 99%
“…Therefore, more research is needed in the future to focus on the direct relationship between infectious factors and psoriasis. In the treatment of psoriasis, nanotechnology enhances the efficiency of local drug delivery and limits the systemic use of immunosuppressive drugs by improving drug penetration [4,29]. If nanotechnology can be used to deliver infection-controlling drugs, it could be a viable and efficient way to treat psoriasis in the future.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…Several studies have shown that pro-inflammatory cytokines in psoriasis, such as IL-6, IL-17, and TNF-α, are associated with psychiatric disorders [27,28]. Second, the microbiota-gut-brain axis can be the potential bridge between infection or microbiota dysbiosis and psychiatric or psychological problems [29]. Patients with depression and anxiety exhibit disturbances in the gut microbiota [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Bidirectional communication between the skin and brain regulates local and global homeostasis in the body [ 1 ]. The skin is the first barrier located at the interface with the external environment, and it senses, collects, and responds to environmental stimuli (such as oxidative stress, ultraviolet (UV) and infrared radiation, and pollution) [ 2 ]. Skin converts these external stresses into cellular signals.…”
Section: Main Textmentioning
confidence: 99%